O zmianach w zakresie leczniczych środków zabezpieczających na tle nowelizacji kodeksu karnego z 2015 roku - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The author presents questions related to the change in the legal regulations concerning selected precautionary measures. She emphasizes the inconsistencies relating to changes in the scope of precautionary measures, especially addiction treatment. The author basically welcomes the changes resulting from the amendment of 20 February 2015, but considering the need to change specific normative solutions concerning addiction therapy.
Keywords: przestępstwo; środek zapobiegawczy; terapia uzależnień; środek odurzający; uzależnienie